RANCANG BANGUN SISTEM PENILAIAN KINERJA LAYANAN KEMAHASISWAAN - Sika, Xaverius (JOURNAL V-TECH (VISION TECHNOLOGY), 2019)
STIKOM Dinamika Bangsa is one of the accredited Colleges in Computer Science in Jambi. But now the competition is increasingly competitive with the emergence of new IT campuses. Therefore, STIKOM Dinamika Bangsa must be able to improve its quality, which is required to be more sensitive to the interests of its stakeholders. The most important internal stakeholders are students who are customers who must be maintained and given the maximum service possible. In its implementation, STIKOM Dinamika Bangsa provides a box of complaints and suggestions for students who want to provide criticism or complaints about existing services. However, this is not enough to be an evaluation of the services that have been provided. To improve student services, a clear assessment of service performance includes all existing student services. This study aims to build a student service performance appraisal system.